Isolasi dan Karakterisasi Bakteri Rizosfer Pohon Kamboja (Plumeria acuminata) di TPU Pracimaloyo sebagai penghasil IAA - Sahasika Sean Putra; Triastuti Rahayu; Erma Musbita Tyastuti (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Cambodian trees are known to be resistant to biotic and abiotic stresses which may be influenced by the presence of rhizosphere bacteria as Plant Growth-Promoting Rhizobacteria (PGPR). This study aims to isolate and characterize Cambodian tree rhizosphere bacteria from burial soils that have the potential to produce IAA. Methods: Rhizospheric soil samples were taken from Pracimaloyo TPU, Surakarta, Central Java, at 5 points attached to the surface of the frangipani tree roots to be inoculated using the scattering cup method at 10-5 and 10-6 dilutions in NA (nutrient agar). After 48 hours, colonies were counted to obtain population data. The ability of rhizosphere bacteria to produce IAA was carried out qualitatively and quantitatively at the age of 24 and 48 hours of culture. Rhizospheric bacteria isolates potential to produce IAA were characterized macroscopically (colony morphology) and microscopically by Gram staining. Results: The population of frangipani tree rhizosphere bacteria in all blocks did not show a significant difference and was detected to have a population between 1.9 – 10.4 x 106. Qualitative test of the ability to produce IAA, it was detected that 34.88% of isolates produced very high IAA. The highest concentration of IAA was produced by isolate P37, followed by P38 and P24 at 48 hours of age, namely 113.58 ppm, 77.95 ppm, and 55.69 ppm. All potential isolates to produce IAA are cocci-shaped gram-negative bacteria. Conclusion: The population of frangipani tree rhizosphere bacteria in Pracimaloyo TPU ranged from 1.9-10.4 x 106 CFU/g and 34.88% had the ability to produce IAA. The concentration of IAA produced was higher at 48 hours of culture compared to 24 hours with the highest concentration by isolate P37 (83.098 ppm and increased to 113.588 ppm). Isolate P37 is a gram-negative cocci-shaped bacterium and irregular colonies.